2012
DOI: 10.1007/s00894-012-1531-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of computational methods for modeling alpha-helical structures

Abstract: Geometry optimization results are reported for secondary structural elements of small proteins and polypeptides. Emphasis is placed on how well molecular mechanics as well as semiempirical, ab initio, and density functional methods describe α-helical and related structures in purely theoretical models (Gly10, Ile10) as well as in realistic models (an α-helical region of calmodulin, and the complete structure of a small protein). Many of the methods examined here were found to provide unsatisfactory description… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…If non-covalent interactions are essential, SQM-DH based refinement of structures might in general be a good idea [96] . Lupan et al for instance found very good results for α -helical structures [97] , also in comparison to DFT methods. Especially PM6-DH + proved valuable as a basis for the non-local optimization of molecular structures, for instance for screening the conformational space of the FGG tripeptide [98] or DNA quadruplex/molecule complexes [99] .…”
Section: Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…If non-covalent interactions are essential, SQM-DH based refinement of structures might in general be a good idea [96] . Lupan et al for instance found very good results for α -helical structures [97] , also in comparison to DFT methods. Especially PM6-DH + proved valuable as a basis for the non-local optimization of molecular structures, for instance for screening the conformational space of the FGG tripeptide [98] or DNA quadruplex/molecule complexes [99] .…”
Section: Applicationsmentioning
confidence: 97%
“…Also many other studies both in life and materials science found the performance of SQM-DH methods similar to DFT-D [84,91,92,97,122,143,144,153,161–166] , sometimes even when aiming for high accuracy in complicated cases (like for instance the interaction of DNA bases with Li@C60 [167] ), but a number of studies (often relying on the older AM1-D or PM3-D models) observe a lower quality of SQM-DH results [168–170] .…”
Section: Applicationsmentioning
confidence: 99%
“…A large number of studies have now shown that SQM-DH methods perform almost as accurately as DFT-D for a wide variety of systems that are dominated by non-covalent interactions [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Furthermore, detailed benchmark studies, in comparison to classical approaches, DFT-D, and highly accurate WFT data is available in the original development papers as well as in separate benchmark studies [ 76 ].…”
Section: Dispersion and Hydrogen Bond-corrected Semi-empirical Quamentioning
confidence: 99%
“…Excellent correlation with experiment was observed, with an R 2 value of 0.9, in comparison to 0.7 for an classical approach. Like DFT-D, SQM-DH methods were shown to be valuable for structure refinement purposes [ 75 , 87 , 88 , 89 , 90 ]. Again, like DFT-D, SQM-DH proved to be an intesting tool for applications in materials science [ 71 , 91 , 92 , 93 , 94 , 95 ], giving some hope for tackling problems at the interface of life and materials science.…”
Section: Dispersion and Hydrogen Bond-corrected Semi-empirical Quamentioning
confidence: 99%
“…The conformational analysis of the phenothiazine unit (folded along an axis passing through the heteroatoms N and S) indicates a preference for a quasi-equatorial orientation of the methyl substituent, but minima with one or both methyl groups in quasi-axial orientation were also identified (Figure 3), which are higher in energy by 5-12 kcal/mol, depending on the method employed. [39] To elucidate the preferred molecular structures in the solid state, single crystals of PTB 5a and 5b that were suitable for X-ray analysis were obtained from ethanol. [39] To elucidate the preferred molecular structures in the solid state, single crystals of PTB 5a and 5b that were suitable for X-ray analysis were obtained from ethanol.…”
Section: Phenothiazine Analogues Of Tröger's Basementioning
confidence: 99%